UTILITY OF SELF GROWN MEDICINAL PLANTS AS TRADITIONAL REMEDY IN FARRUKHABAD DISTRICT - Nikhil Agnihotri (European Journal of Agricultural and Rural Education, 2022)
Utility of plants against disease is quite proved since time immemorial. It is recorded and documented that Indians in ancient times developed and perfected a well organized medicinal system which is closely related with plants. These plants are used as a single drug or as a component of simple or often quite complex proprietary preparation. There are a variety of medicinal plants that are self-grown or wild with rich medicinal properties. The parts of these plants that are used in medicine are bark, roots, seeds, leaves, flowers, fruits, nuts etc. The present study is focused on the role of self-grown medicinal plants as household or folk remedies in the Uttar Pradesh district of Farrukhabad in primary health preservation. 37 plants with their local names, botanical names, ecology, habitat, medicinal utilities and methods of use against diseases are described and analysed in this research. Most of the plants are readily available and useful for more than one disease during the year. We will make therapy cheaper, non-reactive, safer and easily available to all by conserving these valuable plants